TEACHERS’ PERSPECTIVE IN TEACHING VOCABULARY BY USING STORY TECHNIQUE - Fitrawati; Qalby, Nur; Burhanuddin, Wildhan (FKIP Unismuh Makassar, 2024)
This research aims to know the teachers’ perspective in teaching vocabulary by using story technique at Madrasah Tsanawiyah Negeri 2 Enrekang. The research methodology of this research is descriptive qualitative. The technique of collecting data is interview, and record perspectives of the teachers about the using of story technique. Data analysis are transcribing, classifying and concluding. The result of this research found the good perspective of the teachers’ about using story technique in teaching vocabulary at Madrasah Tsanawiyah Negeri 2 Enrekang, especially the used of story techniques really helped teachers in delivering learning material and helped students more easily understand the material presented in the learning process, Story techniques can arouse students' curiosity, instill good educational values for students and can develop students' imaginations. Story technique is often used for some purposes like improving the student’s understanding of the vocabulary material, creating a relaxing and exciting environment of learning and teaching, and creating a good interaction between the class member.